Multi-Response Optimization of Mechanical Properties of Hybrid (Fiberglass / Abaca Woven) in Polyester Matrix using Desirability Function based on DOE. (February 2019) - Paredes, J; Vaca, H; Erazo, H; Pérez, C
Abstract: The study of the application and mechanical behavior of new composite and hybrid materials within the bodywork industry in its different parts (external and internal) has led to perform different characterizations and analysis of results which determined the material with the best mechanical properties in many cases depending on the subjectivity of the researcher. In the present study the optimization of the mechanical properties tensile and flexural hybrid composite made of natural fiber and synthetic fiber was made. To produce the hybrid fabric, abaca (AbF) and cotton (CF) over glass (FG), combined with a polymer matrix polyester resin was used. The configuration of the fibers and the type of drying (ambient and oven), were taken as input factors. The influence of these factors on the overall responses were analyzed using factorial design. A function of desirability was used for the optimization of experimental responses. The results indicated that the optimal factors to take advantage of the experimental responses or mechanical properties, were the configuration of 20% FV + 7.75% FAb (45°) + 2.25% FAI (135°) and the type of oven drying, with a value of global desirability of 0.8208.